2021
DOI: 10.21203/rs.3.rs-149461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Silybin Supplementation on Nutrient Digestibility, Hematological Parameters, Liver Performance, and Liver-specific mi-RNA Concentration in Dogs

Abstract: BackgroundHepatopathies are an important group of disorders in dogs, where proper nutritional care is crucial. Supplementation with a hepatoprotectant like silybin can improve liver performance, subsequently it should not interfere with nutrient digestibility. The purpose of the study was to investigate the effect of either pure silybin or commercial hepatoprotectant on nutrients digestibility, liver performance and health status in healthy dogs (EXP1). Moreover, the second experiment (EXP2) investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The renal histological damage protection effect of SMS extract has been demonstrated by Jaggi et al [5]. In addition, plenty of studies have demonstrated that dietary supplementation of SMS extract had no significant effects on the serum creatinine levels in ducks [36], horses [37], and dogs [29]. Therefore, the results of this study indicated that dietary supplementation of SMS extract had no adverse effects on the renal function in weaned piglets.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The renal histological damage protection effect of SMS extract has been demonstrated by Jaggi et al [5]. In addition, plenty of studies have demonstrated that dietary supplementation of SMS extract had no significant effects on the serum creatinine levels in ducks [36], horses [37], and dogs [29]. Therefore, the results of this study indicated that dietary supplementation of SMS extract had no adverse effects on the renal function in weaned piglets.…”
Section: Discussionsupporting
confidence: 61%
“…The immunostimulatory properties of SMS extract have been reported in human [5,40]. However, the levels of RBC, WBC, IgA, and IgM in blood were not affected by SMS extract supplementation in the diet of dogs [29], broiler chicks [41], and rabbit bucks [42]. At present study, feeding weaned piglets with SMS extract containing diet had no significant effects on the blood immune parameters.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…In other biochemical parameters, the authors observed a decrease in WBC, neutrophils, eosinophils, ALP, glucose, and α -amylase 101 . With minor relevance, an alteration of the serum fatty acid profile (lower concentration of C20:5-n3 and C22:0 and higher concentration of C15:0 and C17:0) was observed 103 . In the same study, in a dog group with hepatopathies, Hepaxan reduced the hepatic miR-122 gene expression 103 .…”
Section: Milk Thistle and Its Derivative Products In Dogs And Catsmentioning
confidence: 99%
“…With minor relevance, an alteration of the serum fatty acid profile (lower concentration of C20:5-n3 and C22:0 and higher concentration of C15:0 and C17:0) was observed 103 . In the same study, in a dog group with hepatopathies, Hepaxan reduced the hepatic miR-122 gene expression 103 . The hepatic damage caused by toxic agents was studied in 1990 by Paulova and colleagues 104 , who tested the efficacy of SIL (100 mg/kg-BW/bid) for treating CCl4-induced liver disease in 16 beagles.…”
Section: Milk Thistle and Its Derivative Products In Dogs And Catsmentioning
confidence: 99%